Gambaran Kualitas Hidup pada Lansia di Perumahan Graha Mustamindo 3 RT.09 Desa Rimbo Panjang - Hardianti, Sri; Virgo, Gusman; Hastuty, Milda (ANTHOR: Education and Learning Journal, 2023)
The purpose of this research is to find out the description of the quality of life of the elderly inGraha Mustamindo Housing 3 Rt. 09 Long Rimbo Village. The approach to this study is descriptive, namely a method that aims to describe the quality of life of the elderly at Graha Mutamindo Housing 3 Rt. 09 Rimbo Panjang Village. This research was conducted from December to January 2022. This research was carried out at Graha Mustamindo Housing 3 Rt. 09 Rimbo Panjang Village with the consideration that Graha Mustamindo Housing 3 Rt. 09 is an area with a lot of elderly people. The population in this study were all the elderly in Graha Mustamindo Housing 3 Rt. 09 Rimbo Panjang village, namely 35 families. the number of samples in the study was 35 respondents to be able to describe the quality of life of the elderly at Graha Mustamindo Housing 3 Rt. 09 Rimbo Panjang Village. The sampling technique in this study was saturated sampling, namely taking all members of the population as samples. This research is descriptive research where research data were obtained by distributing questionnaires to 35 elderly people at Graha Mustamindo Housing 3 RT 09 Rimbo Panjang Village. Based onunivariate analysis, it was found that the quality of life of the elderly in Graha Mustaminedo Housing 3 RT 09 Rimbo Panjang Village, as many as 28 elderly (76.5%) perceived their quality of life to be good, 5 elderly (21.0%) perceived their quality of life to be moderate, 1 elderly (1.2 %) perceive their quality of life as bad, and 1 elderly (1.2%) perceive themselves very badly.